No more dead dogs - Korman, Gordon (New York : Scholastic, 2000)
Eighth grade footbal hero Wallace Wallace is sentenced to detention attecding rehearsals of the school play where, in spite of himself, he becomes wrapped up in the porduction and begins to suggest changes that improve not omly the play but his life as well.
Keywords: Theater -- Fiction; Schools -- Fiction; Football stories -- Fiction